GRAPPA treatment recommendations: updates and methods - Kavanaugh, A; Coates, LC; van der Windt, DA; Corp, N; Soriano, ER (Journal of Rheumatology, 2020)
The development and updating of treatment recommendations for optimal treatment approaches for patients with psoriatic arthritis (PsA) has been an important mission of the Group for Research and Assessment of Psoriasis and PsA (GRAPPA) since its inception. Even though the most recent iteration of the GRAPPA PsA recommendations was completed only a few years ago, there have been many significant advances related to therapies and treatment approaches for PsA since their publication. Because of these advances, the process to update the recommendations again has begun. The standard approaches to guideline (or treatment recommendation) development have also evolved in recent years. Herein, the basis for the approach that will be taken for the next version of the GRAPPA PsA treatment recommendations is reviewed.